Role of AhR and Foxo1 in skin inflammation in burn animal model via MAPK signaling pathway - Li, Kaitong; Fan, Yong; Xu, Zongjie; Xu, Chao (Cellular and Molecular Biology, 2020)
Burn generally refers to thermal damage, including tissue damage caused by hydrothermal (water, soup, oil, etc.), flame, steam, high-temperature gas, hot metal liquid or solid (such as molten steel, ingot). However, little is known about the pathogenesis and inducement of skin inflammation in burned rats. Therefore, this study has carried out an in-depth analysis of the related causes of skin inflammation in burned rats. We analyzed the gene expression and the differentially expressed genes co-expression in burned rats. Subsequently, a set of functional dysfunction modules about inflammation of skin tissue in burned rats were obtained by comprehensive enrichment analysis. In addition, based on related network prediction analysis, we identified a number of regulatory factors, such as endogenous genes, nCRNAs, and transcription factors that have potential monitoring effects on skin inflammation in burned rats. Firstly, we obtained 2679 differentially expressed genes and 7 disease-related dysfunction modules in burned rats. Secondly, we identified a series of regulators related to skin inflammation in burned rats, including 117 ncRNAs (including miR-17-5p, miR-122-5p, and miR-140-5p), 31 transcription factors (including AhR, Foxo1 and Sp1) and 10 endogenous genes (including Il5, Atp5d, and Cox4i1). Core transcription factors AhR and Foxo1 may induce skin inflammation in burned rats through the cascade of MAPK signals. According to the results of this study, we can show a new method for biologists and pharmacists to reveal the inducement of skin inflammation in burned rats and provide a valuable reference for different treatment options.